ANALYSIS OF JUDGE’S DECISION RELATED TO THE TRANSFER OF LAND RIGHTS FOR FOREIGN NATIONALS BASED ON TESTAMENT: (Literature Review of Supreme Court Decision Number 1134K/PDT/2009) - Gregory Ariel Cahya Antareksa; Cokorda Dalem Dahana (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2022)
This study aims to analyze the judge’s decision related to the transfer of Land Rights for Foreign Nationals based on testament of Supreme Court Decision Number 1134K/Pdt/2009. Research questions on this study are based on problematical publishing freehold title based on testament, incidentally between Testator and Testament Recipient at that time both of them is Foreign Nationals has broken the Law Number 5 of 1960 on Basic Agrarian Law Act. This research is normative-descriptive using library research to collect relevant source, such as books, magazines, scientific writing, and others to support the writer’s argument on the issue. The findings revealed that someone can acquire basic consideration of Supreme Court Decision and legal analysis about giving a decision of Supreme Court Decision number 1134K/Pdt/2009. Thus, in the case of Decision No. 1134K/Pdt/2009, the process of transferring ownership of Freehold Title is due to sporadic land registration beginning with the approval of the Head of the Environment, Lurah, and Camat, as well as land owners who are on the right, left, front, and back of the disputed object, so Freehold Title against the object of dispute may be issued on behalf of the Defendant, which is issued by the Land Office. Hence, the parties involved in the intermittent registration, including the Land Office, should be sued, not the Defendant.